Three Different Bolus Doses of Propofol Using Total Intravenous Anaesthesia (TIVA) in Patients Undergoing Transvaginal Oocyte Retrieval: on Table Recovery Time and Time to Discharge Using Post Anaesthesia Discharge Scoring System (PADSS) - MK, Yuvaraj; DS, Aiyappa (Academia Anesthesiologica International, 2019)
Background: The patients undergoing IVF treatment are thoroughly evaluated for the cause of infertility, appropriate treatment instituted and the associated co morbidity. Another major challenge for the anaesthetists is to allay the anxiety. The patients presenting in the IVF clinic are under high degree of social and psychological stress. Detailed pre anaesthetic check up was done a day prior to surgery and appropriate investigations were carried out. Subjects and Methods: The anaesthetic technique and the questionnaire were explained to the patients and an informed written consent was taken from all the patients.Patients were kept fasting overnight prior to surgery and were premedicated with Tab. Ranitidine 150 mg and Tab. Alprazolam 0.25 mg on the night before surgery and repeated on the next day one hour prior to surgery with sip of water. Results: On table recovery time was found to be 6.12 minutes in group P1 (2mg/kg), 5.32 minutes in group P2 (1.5mg/kg) and 5.32 minutes in group P3 (1mg/kg). No statistical difference observed between the 3 groups. Time to discharge was found to be 37.08 minutes in group P1 (2mg/kg), 33.48minutes in group P2 (1.5mg/kg) and 28.88minutes in group P3 (1mg/kg). Conclusion: On table recovery time was found to be 6.12 minutes in group P1 (2mg/kg), 5.32 minutes in group P2 (1.5mg/kg) and 5.32 minutes in group P3 (1mg/kg). No statistical significant difference was observed between the three groups.